A global house price pubble? Evaluation based on a new rent-price approach - Katja Taipalus (Bank of Finland, 2006)
The dividend yield ratio in the stock markets is, to an extent, comparable to the rent-price ratio in the housing market.Taking advantage of this definitional similarity, one can then use the traditional unit root test for log dividend yield in this case, the log rent-price ratio to test for the existence of real estate bubbles.Such unit root tests are conducted for Finland, USA, UK, Spain and Germany, and the simple test results strongly suggest the existence of bubbles in nearly all of these countries.In addition to this, we develop a continuous and monthly rent-price information-based method to track the periods when real estate prices diverge from their fundamental levels.This indicator seems to work quite well in most cases, indicating bubbles during periods which, according to the consensus literature, are seen as periods of sizable upward or downward shifts in house prices.
URN:NBN:fi:bof-20140807333
Keywords: G12; 330; house price; bubble; unit root